Niche specialization in Bromus tectorum seed bank pathogens. Issue 3 (13th June 2018) - Meyer, Susan E.; Beckstead, Julie; Allen, Phil S.
Abstract: Niche theory predicts that when two species exhibit major niche overlap, one will eventually be eliminated through competitive exclusion. Thus, some degree of niche specialization is required to facilitate coexistence. We examined whether two important seed bank pathogens on the invasive winter annual grass Bromus tectorum (cheatgrass, downy brome) exhibit niche specialization. These pathogens utilize seed resources in complementary ways. Pyrenophora semeniperda is specialized to attack dormant seeds. It penetrates directly through the seed coverings. Hyphae ramify first through the endosperm and then throughout the seed. Seed death results as the embryo is consumed. In contrast, the Fusarium seed rot pathogen ( Fusarium sp.) is specialized to attack non-dormant seeds in the early stages of germination. It cannot penetrate seed coverings directly. Instead, it responds to a cue emanating from the radicle end with directional hyphal growth and subsequent penetration at the point of radicle emergence, causing seed death. Non-dormant seeds usually escape P. semeniperda through germination even if infected because it develops more slowly than Fusarium . When water stress slows non-dormant seed germination, both P. semeniperda and Fusarium can attack and cause seed mortality more effectively. The Fusarium seed rot pathogen can sometimes reach epidemic levels and may result in B. tectorum stand failure ('die-off'). Stands usually re-establish from the persistent seed bank, but if P. semeniperda has also reached high levels and eliminated the seed bank, a die-off can persist indefinitely.